2005
DOI: 10.1101/lm.93205
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of memory consolidation by the basolateral amygdala or nucleus accumbens shell requires concurrent dopamine receptor activation in both brain regions

Abstract: Previous findings indicate that the basolateral amygdala (BLA) and the nucleus accumbens (NAc) interact in influencing memory consolidation. The current study investigated whether this interaction requires concurrent dopamine (DA) receptor activation in both brain regions. Unilateral, right-side cannulae were implanted into the BLA and the ipsilateral NAc shell or core in male Sprague-Dawley rats (∼300 g). One week later, the rats were trained on an inhibitory avoidance (IA) task and, 48 h later, they were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 47 publications
(34 reference statements)
4
66
1
1
Order By: Relevance
“…Studies have shown that post-training injections of dopamine receptor agonists and antagonists into the nucleus accumbens, respectively, facilitate and disrupt associative learning involving both positive and negative incentive stimuli (Setlow and McGaugh, 1998;Dalley et al, 2005;LaLumiere et al, 2005). Our data suggest that rats can learn conditioned place aversion under severe inhibition of medial A10 neurons, bringing into question the idea that dopamine, at least in the terminal regions of these neurons, is required for or facilitates learning per se.…”
Section: How Do Medial A10 Neurons Mediate Stimulusincentive Learning?mentioning
confidence: 67%
“…Studies have shown that post-training injections of dopamine receptor agonists and antagonists into the nucleus accumbens, respectively, facilitate and disrupt associative learning involving both positive and negative incentive stimuli (Setlow and McGaugh, 1998;Dalley et al, 2005;LaLumiere et al, 2005). Our data suggest that rats can learn conditioned place aversion under severe inhibition of medial A10 neurons, bringing into question the idea that dopamine, at least in the terminal regions of these neurons, is required for or facilitates learning per se.…”
Section: How Do Medial A10 Neurons Mediate Stimulusincentive Learning?mentioning
confidence: 67%
“…Prior studies indicate that the BLA modulates the consolidation for many different types of learning including inhibitory avoidance (LaLumiere et al 2004(LaLumiere et al , 2005, CFC Huff and Rudy 2004), conditioned taste aversion (Miranda et al 2003;Guzman-Ramos and Bermudez-Rattoni 2012), spatial and cued-response learning (Packard et al 1994), and novel object recognition (Roozendaal et al 2008;Bass et al 2012). However, evidence also indicates that different types or kinds of learning involve separate and distinct brain regions, as, for example, the hippocampus and caudate are involved in the consolidation of spatial and cued water maze learning, respectively (Packard et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The findings that DA is also involved in aversive conditioning by LiCl (Di Chiara, 2002) and fear conditioning (Nader and LeDoux, 1999;Pezze and Feldon, 2004) support its role in associative learning and memory consolidation. Blockade of D1-like and D2-like DA receptors interferes with consolidation of Pavlovian conditioned behavior (Greba et al, 2001;Koch et al, 2000;LaLumiere et al, 2005;Nader and LeDoux, 1999). Given that METH neurotoxicity diminishes levels of corticostriatal and mesolimbic DA, we first sought to investigate if posttraining administration of D1 and D2 DA receptor agonist improves consolidation of cocaine CPP.…”
Section: Introductionmentioning
confidence: 99%